The D-dimer level predicts the postoperative prognosis in patients with non-small cell lung cancer - Shiina, Yuki; Nakajima, Takahiro; Yamamoto, Takayoshi; Tanaka, Kazuhisa; Sakairi, Yuichi; Wada, Hironobu; Suzuki, Hidemi; Yoshino, Ichiro (PloS one, 2019)
Carcinoma cells often modulate coagulation and fibrinolysis among cancer patients. Plasma dimerized plasmin fragment D (D-dimer) has been reported as a prognostic marker of various types of malignancies, including non-small cell lung cancer (NSCLC). However, the associations between the plasma D-dimer level and peripheral small NSCLC remain unclear. Three hundred and sixty-two patients with NSCLC who underwent radical surgery were retrospectively reviewed. Patients who received anticoagulation therapy before surgery or who lacked preoperative D-dimer data were excluded. The other 235 patients were divided into a high D-dimer (over 1.0 μg/mL) group (HDD group, n = 47) and a normal D-dimer group (NDD group, n = 188) and investigated for their clinical characteristics, computed tomography (CT) findings, pathological findings, and clinical outcomes. The mean D-dimer levels was 2.49±2.58 μg/ml in the HDD group and 0.42±0.23 μg/ml in the NDD group. The HDD group was characterized by a predominance of male gender, older age, pure solid appearance on chest CT, vascular invasion in pathology, and a large solid part of the tumor. The HDD group showed a worse overall survival, disease-free survival, and disease-specific survival than the NDD group (p<0.001, <0.001, <0.001, respectively). These survival features were also observed in p-Stage IA disease. There was no marked survival difference when tumors showed ground-glass opacity on CT. In NSCLC patients with a solid tumor appearance on CT, high D-dimer levels predict a poor survival and early recurrence.